Cyclotron resonance of a two-dimensional Wigner solid - Monarkha, Yu. P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Cyclotron resonance absorption from a two-dimensional electron solid formed on a free surface of liquid helium is analyzed by means of the memory function formalism. The presence of the low-frequency phonon mode of the Wigner solid in a strong magnetic field is shown to broaden significantly the electron dynamical structure factor (DSF) as a function of frequency, strengthening the contribution from multi-phonon emission terms of the high-frequency mode. Thus in most cases the linewidth is formed by nonlinear terms of the DSF expansion in the cyclotron motion factor exp (-iwct) rather than by the linear terms analyzed previously. The inclusion of all these multi-phonon terms changes the sign of the many-electron effect and agrees well with available experimental data, eliminating the discrepancy between theory and experiment.